Speckle Filtering and Physical Scattering Decomposition for ALOS-2 PALSAR-2 Polarimetric Mosaic - LEE KEN YOONG (Asian Association on Remote Sensing, 2021)
Proceedings of the 42nd Asian Conference on Remote Sensing